Stable Isotopes Constrain Water Seepage From Gnammas Into Bare Granitic Bedrock - J. O. Albrigtsen; B. A. Wing; R. C. Glade; R. S. Anderson (Geophysical Research Letters)
Abstract Subtle bedrock depressions called gnammas allow the water in ephemeral pools to maintain contact with bare rock, thus serving as natural rock‐weathering experiments. Following filling by precipitation, evaporation is often assumed to be the sole process of water loss from gnammas. We evaluated this assumption by monitoring evolving stable isotope compositions of gnamma waters hosted in granite of Colorado's Front Range. Surprisingly, we found that a significant fraction of the water was lost by seepage through the underlying bedrock. Seepage dominated, with only 10%–20% loss by evaporation. We propose a conceptual model of gnamma formation in which enhanced weathering of the bedrock beneath the gnamma increases the water holding capacity and permeability of the underlying rock that in turn promotes efficient water loss through seepage and further weathering of the surrounding rock. This model has implications for bare‐rock weathering and hence the evolution of landscapes over geologic timescales.